2021
DOI: 10.3390/insects12070656
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Phylogenetic Relationships among Three Subfamilies within Heptageniidae (Insecta: Ephemeroptera) along with Low-Temperature Selection Pressure Analyses Using Mitogenomes

Abstract: We determined 15 complete and two nearly complete mitogenomes of Heptageniidae belonging to three subfamilies (Heptageniinae, Rhithrogeninae, and Ecdyonurinae) and six genera (Afronurus, Epeorus, Leucrocuta, Maccaffertium, Stenacron, and Stenonema). Species of Rhithrogeninae and Ecdyonurinae had the same gene rearrangement of CR-I-M-Q-M-ND2, whereas a novel gene rearrangement of CR-I-M-Q-NCR-ND2 was found in Heptageniinae. Non-coding regions (NCRs) of 25–47 bp located between trnA and trnR were observed in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 93 publications
9
25
0
Order By: Relevance
“…The nucleotide compositions of the two mitogenomes are summarized in Table 2. Both whole mitogenomes were biased in base composition ((A + T)% > (G + C)%), which is consistent with the genomes from other insects [25]. The A + T content of the complete sequence was 73.38% for P. edmundsi and 73.07% for P. projecta (Table 2).…”
Section: Nucleotide Compositionsupporting
confidence: 79%
See 2 more Smart Citations
“…The nucleotide compositions of the two mitogenomes are summarized in Table 2. Both whole mitogenomes were biased in base composition ((A + T)% > (G + C)%), which is consistent with the genomes from other insects [25]. The A + T content of the complete sequence was 73.38% for P. edmundsi and 73.07% for P. projecta (Table 2).…”
Section: Nucleotide Compositionsupporting
confidence: 79%
“…However, our previous study using mitogenomes showed that Leptophlebiidae was clustered with the group (Caenidae + Baetidae) [24]. In the newly published research by Xu et al (2021), the results placed Caenidae as a sister group of (Baetidae + Teloganodidae) and Leptophlebiidae was then consolidated together [25]. Over the past decade, multiple phylogenetic trees using mitogenomes were reconstructed and all of these included only a subset of Ephemeroptera families due to a lack of taxon sampling [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insect mt genomes are usually double-stranded circular molecules of 14–20 kb in length, encoding 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs), and a control region (CR; AT-rich region) [ 2 ]. Many researchers have stimulated great interest in the insects’ mt genome including testing hypotheses about microevolution, mt gene expression, population structure analysis, phylogenetic relationships, and identification of cryptic species [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Since William Derham discovered the first cryptic species in 1718, these species are still a principal subject of several research areas and actually have a history of 300 years [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, various studies of mammalian [ 34 , 35 ], avian [ 36 ], frog [ 33 ], fish [ 37 ], and insect mitogenomes have indicated that adaptive evolution has occurred. Among insects, this has included studies of Hymenoptera [ 38 ], Orthoptera [ 39 ], Ephemeroptera [ 40 ], Diptera [ 41 ], and Lepidoptera [ 42 ]. Thus, the mitogenome can be used as a molecular tool to explore/assess adaptive evolution.…”
Section: Introductionmentioning
confidence: 99%